Exosomes From Human Umbilical Cord Mesenchymal Stem Cells Treat Corneal Injury via Autophagy Activation - Ma, Shisi; Yin, Jiayang; Hao, Lili; Liu, Xiao; Shi, Qi; Diao, Yuyao; Yu, Guocheng; Liu, Lian; Chen, Jiansu; Zhong, Jingxiang (Frontiers in Bioengineering and Biotechnology, 2022)
Corneal injury (CI) affects corneal integrity and transparency, deteriorating the patient's quality of life. This study aimed to explore the molecular mechanisms by which exosomes secreted from human umbilical cord mesenchymal stem cells (hucMSC-Exos) affect autophagy in human corneal epithelial cells (HCECs) and CI models. We isolated and identified hucMSC-Exos using nanoparticle tracking analysis, transmission electron microscopy, and western blotting. The effects of hucMSC-Exos combined with autophagy regulators on HCECs and CI mice were assessed using cell viability assays, scratch assay, cell cycle assay, apoptosis assay, corneal ﬂuorescein staining, haze grades, pathological examinations, western blotting, and quantitative polymerase chain reaction (qPCR). In vitro results indicated that hucMSC-Exos combined with the autophagy activator had positive effects in promoting the cell proliferation, migration capacity, and the cell cycle by upregulating the proportions of cells in the S phase and the expression of PCNA, Cyclin A, Cyclin E, and CDK2. Meanwhile, the combination treatment reduced the apoptotic rate of HCECs. In vivo results indicated that hucMSC-Exos especially combined them with the autophagy activator significantly alleviated corneal epithelial defects and stromal opacity, reduced the levels of the apoptotic markers Bax and cleaved Caspase-3, reduced the inﬂammatory response products TNF-α, IL-1β, IL-6, and CXCL-2, and increased the Bcl-2. This was achieved by upregulating pAMPK/AMPK and pULK1/ULK1 ratios, and Beclin-1 and LC3B II/I, and by downregulating the pmTOR/mTOR ratio and p62. In contrast, clinical indications, apoptosis, and inﬂammation were aggravated after the application of the autophagy inhibitor. HucMSC-Exos combined with an autophagy activator significantly enhanced HCECs functions and alleviated corneal defects, apoptosis, and inflammation by activating the autophagy signaling pathway, AMPK-mTOR-ULK1, providing a new biological therapy for corneal wound healing and ocular surface regeneration.